Analysis of Income and Business Feasibility at Umbu Bahi's Broiler Chicken Farm in Kambajawa Village - Nanchy Rambu Leki; I Made Adi Sudarma (JURNAL PETERNAKAN SABANA, 2023)
This study aims to determine the income of broiler breeders with an independent system in the Kambajawa village. The data collection method is through a case study on one of the broiler breeders, Mr. Umbu Bahi. This research activity uses the interview method and direct data collection in the field at Mulan from October 2022 to March 2023. The research variables analyzed include: total costs, total revenue, total income, R/C ratio, and B/C ratio. Data analysis used descriptive analysis for 1 year when the livestock business was run. The results showed that the average total income of Mr. Umbu Bahi's broiler breeders was IDR 99,780,000 / year with an average monthly income of IDR 8,315,000 / month, the R/C ratio was 1.48 and the value B /C ratio of 0.48.